A PARALLEL IMPLEMENTATION OF A TWO-DIMENSIONAL HYDRODYNAMIC MODEL FOR MICROWAVE SEMICONDUCTOR DEVICE INCLUDING INERTIA EFFECTS IN MOMENTUM RELAXATION - Al-Sunaidi, M. A. (1997)
A self-consistent numerical transport model based on the hydrodynamic equations obtained from Boltzmann's transport equation (BTE) is presented. The model includes both the temporal and spatial variation in electron velocity. A parallel implementation of the solution method, using FDTD techniques, is illustrated. Numerical results for a GaAs MESFET device are generated using this complete hydrodynamic model (CHM) and compared with results obtained from the more commonly used energy or simplified hydrodynamic model (SHM). The results indicate that for short gate-lengths (less than 05 m) the two models lead to different DC steady-state results which in turn lead to different microwave small-signal models for the device.